Pengaruh PDB per Kapita dan Konsumsi Energi terhadap Emisi GRK di Indonesia - Nadeak, Sarwono Alfian H.; Nasrudin, Nasrudin (UI Scholars Hub, 2023)
The purpose of this research is to analyze the effect of GDP per capita and energy consumption on greenhouse gas emissions and test the hypothesis of the Environmental Kuznets Curve (EKC) in Indonesia. This study uses two methods, namely Error Correction Mechanism (ECM) and Autoregressive Distributed Lag (ARDL) with bound testing approach. The results showed that GDP per capita had a positive effect on greenhouse gas emissions. Renewable energy consumption negatively affects greenhouse gas emissions, while non-renewable energy consumption negatively affects total greenhouse gas emissions, but positively influences CO2 emissions. In the long run, the EKC hypothesis applies in Indonesia.